Yanomami indigenous emergency through an anti-corruption perspective - de Sá Souza, Marina Marques; Veras Neto, Francisco Quintanilha (Ius Humani. Jornal do direito, 2025)
The article investigates the Yanomami indigenous emergency, declared in January 2023 by the Brazilian federal government, through practices of corruption: illegal mining, bribery, capture of public policies, and extortion. The study " Fragile Land Governance, Fraud, and Corruption: A Fertile Ground for Land Grabbing," conducted by Transparency International - Brazil (TI), serves as a conceptual basis for defining and identifying corrupt practices in the Yanomami Indigenous Land (TIY). The violation of rights to access to justice and participation is also examined in light of the dismantling of the National Indigenous Peoples Foundation (Funai) and the lack of protection for environmental rights defenders. An empirical, bibliographic, and document analysis research approach is adopted. The study concludes that while integrity actions, and measures to prevent and combat corruption, can be adopted to tackle illegal mining in TIY, it is necessary to incorporate into the discussion and praxis of the collectives defending indigenous rights the contradictory understanding of the legal form as a maintainer of the structure that detaches indigenous peoples and traditional communities from their territories.